Distinguishing fine details by Fresnel domain diffraction (2004)
ABSTRACT: The capability of distinguishing fine details in simple structures by means of Fresnel domain diffraction is shown. Through numerical simulations it is s hown that t he b igger Fresnel's number in the diffraction c onsidered the bigger differentiability is reached. A circular clear aperture with two fine details is employed for illustrating.